2014
DOI: 10.1093/ejcts/ezu378
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin administration for prevention of cardiac surgery-associated acute kidney injury: a meta-analysis of randomized controlled trials

Abstract: The effect of erythropoietin (EPO) on the prevention of cardiac surgery-associated acute kidney injury (CSA-AKI) is controversial. Therefore, we undertook the meta-analysis of randomized controlled trials (RCTs) to assess the efficacy and safety of EPO on the prevention of CSA-AKI in adult patients and to explore whether risk factors for AKI could explain the inconsistent effects. PubMed and EMbase databases were searched to identify eligible RCTs. The meta-analysis was performed with fixed- or random-effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
1
12
0
1
Order By: Relevance
“…A recent meta-analysis (5 studies, 423 patients) found no effect of erythropoietin on the incidence of AKI: RR 0.64 (0.35–1.16). Surprisingly, a preplanned subgroup analysis found a significant reduction of AKI in patients without high risk for AKI: RR 0.37 (0.24–0.61; p  < 0.0001) [211]. Similar results were obtained in the most recent meta-analysis, which in addition showed more protection with pre-anaesthetic administration [212].…”
Section: Hormonal Manipulationsupporting
confidence: 57%
“…A recent meta-analysis (5 studies, 423 patients) found no effect of erythropoietin on the incidence of AKI: RR 0.64 (0.35–1.16). Surprisingly, a preplanned subgroup analysis found a significant reduction of AKI in patients without high risk for AKI: RR 0.37 (0.24–0.61; p  < 0.0001) [211]. Similar results were obtained in the most recent meta-analysis, which in addition showed more protection with pre-anaesthetic administration [212].…”
Section: Hormonal Manipulationsupporting
confidence: 57%
“…A meta-analysis with patients at risk for AKI showed no benefit of ESAs on incidence of AKI [58]. Another meta-analyses of effects of ESAs on CKD patients also showed no clear benefit on progression to RRT, comparing ESA treatment to no treatment [59] or comparing high vs low Hb targets [60, 61], nor was there was an association between ESA dose and annual GFR change or progression to ESRD [62].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative. Numerous pharmacological agents including levosimendan, [94][95][96][97] statins, 98-100 N-acetylcysteine, [101][102][103][104] sodium bicarbonate, [105][106][107][108] and erythropoietin [109][110][111][112][113] have, for the most part, failed to demonstrate benefit for the prevention of CS-AKI. A possible exception is dexmedetomidine, for which a number of small or low-quality studies found a reduction in the occurrence of AKI after cardiac surgery.…”
Section: Pharmacological Strategiesmentioning
confidence: 99%